Libidinal attitudes in women (self pleasure and self punishment) yield to a glamorous and more elastic skin - Lorenzo Martini (Our Dermatology Online, 2023)
Nowaday a new fashion exploded in US and other European countries: self pleasure in women (young or less young) guarantees a visco-elastic property to skin, and glamour and glow to the external appearance. This costume is spread through the brilliant world of actresses and movie stars, but more and more girls are trying to appropriate this attitude in order to attempt to remain always young and fashionable. The A recruited two women (the former elder and the latter younger) and prayed them to watch at porn magazins for two hours in one day and have self-plasure laying down on a couch calmly and serenely, and had the way to measure the visco-elasticity before and after the "amusement" by a Cutometer.